2023
DOI: 10.1136/bmjopen-2022-068122
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review protocol on the impact of antimicrobial resistance on cancer management and outcomes

Abstract: IntroductionAntimicrobial resistance (AMR) is a growing global public health concern and is becoming a significant challenge in the management of patients with cancer. Due to the immunosuppressive nature of cancer treatment, infection is a common complication and the necessary high usage of antibiotics increases the risk of AMR. Failure to adequately prevent and treat infection in patients with cancer as a result of AMR can increase the morbidity and mortality of the disease. The objective of this scoping revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…On the other hand, we had only few cancer patients in the study as the study was done in a general ward setting. Cancer is a recognized immune suppressive condition including the immune suppressive effect of its treatment while surgery or bone marrow related cancer treatments rely on effective infection prevention or treatment (34). Fifty percent (50%) of cancer deaths are due to infections but deaths due to AMR have not been well described (35).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we had only few cancer patients in the study as the study was done in a general ward setting. Cancer is a recognized immune suppressive condition including the immune suppressive effect of its treatment while surgery or bone marrow related cancer treatments rely on effective infection prevention or treatment (34). Fifty percent (50%) of cancer deaths are due to infections but deaths due to AMR have not been well described (35).…”
Section: Discussionmentioning
confidence: 99%
“…15 Other than the high mortality and morbidity risk, CLABSIs also influence antimicrobial resistance, which is significantly higher in oncology patients than in nononcology counterparts, adding another layer of complexity. 16,17 Hamilton Health Sciences (HHS) is a network of 7 hospitals and an oncology center located in Hamilton, Ontario, Canada, providing health care services to the surrounding Hamilton and Niagara regions. In the past, the CLABSI corporate rates at HHS were 3.00/1000 catheter days in critical care settings.…”
Section: Introductionmentioning
confidence: 99%
“…New data from Canada have confirmed that patients with CLABSIs face an increased mortality risk, with 1 in 3 patients succumbing within 30 days of the initial positive culture 15. Other than the high mortality and morbidity risk, CLABSIs also influence antimicrobial resistance, which is significantly higher in oncology patients than in nononcology counterparts, adding another layer of complexity 16,17…”
Section: Introductionmentioning
confidence: 99%